2020
DOI: 10.3390/su12145496
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Sustainable Development Trends and Customer Value Management

Abstract: The sustainable development movement is an essential trend that can resist the excessive consumption and over-exploitation of resources. There have been considerable changes in the perception of the term “sustainable development” over the last 30 years. Difficulties in implementing the principles of rational use of natural resources have resulted from a general conflict between the objectives of economic development and the increasing dynamics of industrial production, the quality of the environment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…However, measuring sustainability and performance during usage is becoming increasingly relevant [106]. The strategies to incorporate the concept of sustainable development must be established [107]. Moreover, VM can perform an effective method for achieving building sustainability.…”
Section: Vm Activities Implementation For Building Sustainable Successmentioning
confidence: 99%
See 1 more Smart Citation
“…However, measuring sustainability and performance during usage is becoming increasingly relevant [106]. The strategies to incorporate the concept of sustainable development must be established [107]. Moreover, VM can perform an effective method for achieving building sustainability.…”
Section: Vm Activities Implementation For Building Sustainable Successmentioning
confidence: 99%
“…In the sustainability sense of construction firms, it was found that they face several obstacles as they mature and have a positive social, environmental and economic impact [117]. These firms should also search for swift and new means of sustaining customer confidence [107]. The proposed VM activities give these companies practitioners the opportunity to take a good decision for achieving their company's success.…”
Section: Vm Activities Implementation For Building Sustainable Successmentioning
confidence: 99%
“…[118]. It is necessary to develop strategies for incorporating the concept of sustainable and performance development [119,120]. Moreover, BIM implementation can carry out an efficient technique of attaining building performance.…”
Section: Discussionmentioning
confidence: 99%
“…The development of processes related to increasing customer involvement has been accompanied by the emergence of the concept of socioeconomic sustainability, which regulates aspects related to the delivery of customer value [46,47]. Sustainability is very important for all "aware customers", i.e., the customers who make their purchasing choices consciously, and in consideration of sustainable development goals (5 × P): people, planet, prosperity, peace, and partnership, as specified by the UN [47,48]. Such customers follow trends influenced by the current sustainable development concerns, which in turn increases their awareness and creates a trend towards (increased) involvement in customerprovider relationships [1,2].…”
Section: Sustainability Development Perspectivementioning
confidence: 99%